Expression of long noncoding RNA Xist is induced by glucocorticoids - Su, Yun; Chen, Xing; Zhou, Hongyan; Shaw, Sean; Chen, Jie; Isales, Carlos M.; Zhao, Jing; Shi, Xingming (Frontiers in Endocrinology, 2022)
Glucocorticoids (GCs) are potent anti-inflammatory and immunosuppressive agents. However, their clinical usage is limited by severe multisystemic side effects. Glucocorticoid induced osteoporosis results in significant morbidity and mortality but the cellular and molecular mechanisms underlying GC-induced bone loss are not clear. GC use results in decreased osteoblast differentiation with increased marrow adiposity through effects on bone marrow stem cells. GC effects are transduced through its receptor (GR). To identify novel GR regulated genes, we examined the profile of genes differentially expressed in GR knockout mouse bone marrow mesenchymal stem cells (MSCs) by RNA sequencing (RNA-Seq) analysis. Results showed 15 upregulated genes (3- to 10-fold) and 70 downregulated genes (-2.7- to -10-fold), with the long noncoding RNA X-inactive specific transcript (Xist) downregulated the most. The differential expression of genes measured by RNA-Seq was validated by qRT-PCR analysis of selected genes and the GC/GR signaling-dependent expression of Xist was further demonstrated by GC (dexamethasone) treatment of GR-deficient MSCs in vitro and by GC injection of C57BL/6 mice (males and females) in vivo. Our data revealed that the long noncoding RNA Xist is a GR regulated gene and its expression is induced by GC both in vitro and in vivo. To our knowledge, this is the first evidence showing that Xist is transcriptionally regulated by GC/GR signaling.